Flexural performance and life-cycle assessment of multi-generation recycled aggregate concrete beams. (1st August 2022) - Visintin, P.; Dadd, L.; Ul Alam, M.; Xie, T.; Bennett, B.
Abstract: To minimize the consumption of virgin aggregates during concrete production, and to utilize the high volume of construction waste, a limited number of studies have been devoted to the potential use of multi-generation recycled aggregate concrete (MGRAC). To date, these studies have been restricted to quantifying aggregate and material properties, and no research has investigated behaviour at the member level or assessed the applicability of code specified design approaches. To investigate the impact of MGRAC at the member level, in this work, four generations of concrete are manufactured, the first using virgin aggregates (VA) and then three subsequent recycled aggregate generations (RA-1 to RA-3) with 100% replacement ratios. The flexural behaviour of MGRAC is tested through a series of small-scale reinforced concrete beams, where for each generation beams with two different reinforcement ratios are tested. Throughout testing, member load-deflection and crack-width are recorded. The study further assesses the feasibility of using standard code approaches to design MGRAC beams at different limit states and quantifies the global warming potential (GWP) of each generation of concrete. The results show member level behaviour at the ultimate limit state is not negatively impacted by the use of MGRAC, but tension stiffening and cracking are influenced at the serviceability limit state. Standard design approaches are able to predict member strength but under predict member deflection. Life-cycle assessment demonstrates little variation in GWP between each generation of concrete manufacture, but as expected, show significant savings in virgin material usage.